The Effect of Investigative Audit, Forensic Accounting and Whistleblowing System on Fraud Disclosure with Spiritual Intelligence as A Moderator - Arham Rasyid Andi Kunna; Amiruddin Amiruddin; Aini Indijawati (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to analyze the effect of investigative audits, forensic accounting, and whistleblowing systems on fraud disclosure with the moderating role of spiritual intelligence. The population of this study were 118 auditors from the Representative Office of the Financial and Development Supervisory Agency (BPKP) of South Sulawesi Province. The purposive sampling method was used, selecting auditors with a minimum service period of 3 years, resulting in a sample of 74 people. A total of 69 returned questionnaires were successfully processed. The data were analyzed using (MRA) and processed with software (SPSS). The results showed that investigative audits, forensic accounting, and whistleblowing systems have a positive effect on fraud disclosure. In addition, spiritual intelligence moderates the effect of investigative audits and whistleblowing systems on fraud disclosure but does not moderate the effect of forensic accounting.